AI Literacy and Workforce Readiness in The Digital Era: The Mediating Role of Human Capital Development - Faisal Hamid Maka Raja; Daeng Ayub; M. Jais; Tri Handoko (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
Artificial intelligence (AI) has become an integral component of higher education and is increasingly recognized as a strategic competency required for future employment. However, although university students frequently utilize AI technologies, limited empirical evidence explains how AI literacy contributes to workforce readiness through the development of human capital. This study aims to examine the direct effects of AI Literacy on Human Capital Development and Workforce Readiness, as well as the mediating role of Human Capital Development in the relationship between AI Literacy and Workforce Readiness among university students. A quantitative explanatory research design was employed using a census sampling technique involving 200 active students from the Community Education Study Program, Faculty of Teacher Training and Education, Universitas Riau, Indonesia. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that AI Literacy positively influences Human Capital Development and Workforce Readiness, while Human Capital Development also exerts a significant positive effect on Workforce Readiness and partially mediates the relationship between AI Literacy and Workforce Readiness. These findings demonstrate that AI Literacy extends beyond technological competence by strengthening students' human capital and enhancing their readiness for the digital workforce. Therefore, higher education institutions should integrate AI literacy into teaching and learning practices to foster graduate competitiveness and sustainable workforce preparedness in the era of digital transformation.